2021
DOI: 10.1159/000515280
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of 2nd- and 3rd-Line Regorafenib for Advanced Hepatocellular Carcinoma

Abstract: <b><i>Introduction:</i></b> This study compared clinical outcomes of 2nd- and 3rd-line regorafenib in patients with unresectable hepatocellular carcinoma. <b><i>Methods:</i></b> In this retrospective cohort study, 48 patients were treated with regorafenib for unresectable hepatocellular carcinoma. Thirty-five and 13 patients were initiated on 2nd- and 3rd-line therapy, respectively. We assessed the responses to and safety of the therapy. <b><i>Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…A search of the PubMed database identified 24 cohorts in 23 studies encompassing 2074 patients treated with REG (Figure 1 and Table ) 11,14–35 . Similarly, six cohorts from six studies comprising 621 patients treated with RAM 12,36–40 were identified, as well as seven cohorts from six studies involving 1240 patients treated with CAB 13,23,33,41–43 (Figure 1 and Tables and , respectively).…”
Section: Resultsmentioning
confidence: 99%
“…A search of the PubMed database identified 24 cohorts in 23 studies encompassing 2074 patients treated with REG (Figure 1 and Table ) 11,14–35 . Similarly, six cohorts from six studies comprising 621 patients treated with RAM 12,36–40 were identified, as well as seven cohorts from six studies involving 1240 patients treated with CAB 13,23,33,41–43 (Figure 1 and Tables and , respectively).…”
Section: Resultsmentioning
confidence: 99%
“…A pivotal randomized, double-blind, placebo-controlled phase 3 trial ( 7 ) substantiated the significant enhancement of overall survival (OS) in patients with progressive HCC after sorafenib treatment. Consequently, it was approved as a pioneering second-line targeted therapy, with subsequent clinical trials corroborating its efficacy in patients with late-stage HCC ( 8 ).…”
Section: Introductionmentioning
confidence: 99%